Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 2: \(a,\frac{7x-1}{2x^2+6x}=\frac{7x-1}{2x\left(x+3\right)}=\frac{\left(7x-1\right)\left(x-3\right)}{2x\left(x+3\right)\left(x-3\right)}\)
\(\frac{5-3x}{x^2-9}=\frac{5-3x}{\left(x-3\right)\left(x+3\right)}=\frac{\left(5-3x\right)2x}{2x\left(x-3\right)\left(x+3\right)}\)
\(b,\frac{x+1}{x-x^2}=\frac{x+1}{x\left(1-x\right)}=-\frac{x+1}{x\left(x+1\right)}=-\frac{2\left(x-1\right)\left(x+1\right)}{2x\left(x-1\right)^2}\)
\(\frac{x+2}{2-4x+2x^2}=\frac{x+2}{2\left(x-1\right)^2}=\frac{2x\left(x+2\right)}{2x\left(x-1\right)^2}\)
\(c,\frac{4x^2-3x+5}{x^3-1}=\frac{4x^2-3x+5}{\left(x-1\right)\left(x^2+x+1\right)}\)
\(\frac{2x}{x^2+x+1}=\frac{2x\left(x-1\right)}{\left(x-1\right)\left(x^2+x+1\right)}\)
\(\frac{6}{x-1}=\frac{6\left(x^2+x+1\right)}{\left(x-1\right)\left(x^2+x+1\right)}\)
\(d,\frac{7}{5x}=\frac{7.2\left(2y-x\right)\left(2y+x\right)}{2.5x\left(2y-x\right)\left(2y+x\right)}\)
\(\frac{4}{x-2y}=-\frac{4}{2y-x}=-\frac{4.2.5x\left(2x+x\right)}{2.5x\left(2y-x\right)\left(2y+x\right)}\)
\(\frac{x-y}{8y^2-2x^2}=\frac{x-y}{2\left(4y^2-x^2\right)}=\frac{x-y}{2\left(2y-x\right)\left(2y+x\right)}=\frac{5x\left(x-y\right)}{2.5x.\left(2y-x\right)\left(2y+x\right)}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{x}{x-2y}+\frac{x}{x+2y}+\frac{4xy}{4y^2-x^2}\)
\(=\frac{x\left(x+2y\right)}{\left(x-2y\right)\left(x+2y\right)}+\frac{x\left(x-2y\right)}{\left(x-2y\right)\left(x+2y\right)}+\frac{-4xy}{\left(x-2y\right)\left(x+2y\right)}\)
\(=\frac{x^2+2xy+x^2-2xy-4xy}{\left(x-2y\right)\left(x+2y\right)}\)
\(=\frac{2x^2-4xy}{\left(x-2y\right)\left(x+2y\right)}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có: \(\frac{x^2y+2xy^2+y^3}{2x^2+xy-y^2}\)
\(=\frac{x^2y+xy^2+xy^2+y^3}{2x^2+2xy-xy-y^2}\)
\(=\frac{xy\left(x+y\right)+y^2\left(x+y\right)}{2x\left(x+y\right)-y\left(x+y\right)}\)
\(=\frac{\left(x+y\right)\left(xy+y^2\right)}{\left(2x-y\right)\left(x+y\right)}=\frac{xy+y^2}{2x-y}\left(đpcm\right)\)
Ta có: \(\frac{x^2+3xy+2y^2}{x^3+2x^2y-xy^2-2y^3}\)
\(=\frac{x^2+xy+2xy+2y^2}{x^2\left(x+2y\right)-y^2\left(x+2y\right)}\)
\(=\frac{x\left(x+y\right)+2y\left(x+y\right)}{\left(x^2-y^2\right)\left(x+2y\right)}\)
\(=\frac{\left(x+2y\right)\left(x+y\right)}{\left(x+y\right)\left(x-y\right)\left(x+2y\right)}=\frac{1}{x-y}\left(đpcm\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(=\frac{16+x}{x^2-2x}-\frac{18}{x^2-2x}\)
\(=\frac{16+x-18}{x\left(x-2\right)}\)
\(=\frac{-2+x}{x\left(x-2\right)}\)
a) \(\frac{16+x}{x^2-2x}+\frac{18}{2x-x^2}=\frac{16+x-18}{x^2-2x}=\frac{x-2}{x\left(x-2\right)}=\frac{1}{x}\)
b) \(\frac{2y}{2x^2-xy}+\frac{4x}{xy-2x^2}=\frac{2y-4x}{2x^2-xy}=\frac{-2\left(2x-y\right)}{x\left(2x-y\right)}=\frac{-2}{x}\)
c) \(\frac{4-x^2}{x-3}+\frac{2x-2x^2}{3-x}+\frac{5-4x}{x-3}=\frac{4-x^2+2x^2-2x+5-4x}{x-3}=\frac{x^2-6x+9}{x-3}=\frac{\left(x-3\right)^2}{x-3}=x-3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) MTC : \(\left(x+1\right)\left(x^2-x+1\right)\)
Quy đồng :
\(\frac{x-1}{x^3+1}=\frac{x-1}{\left(x+1\right)\left(x^2-x+1\right)}\)
\(\frac{2x}{x^2-x+1}=\frac{2x\left(x+1\right)}{\left(x+1\right)\left(x^2-x+1\right)}\)
\(\frac{2}{x+1}=\frac{2\left(x^2-x+1\right)}{\left(x+1\right)\left(x^2-x+1\right)}\)
b ) MTC : \(10x\left(2y-x\right)\left(2y+x\right)\)
\(\frac{7}{5x}=\frac{7.2.\left(2y-x\right)\left(2y+x\right)}{10x\left(2y-x\right)\left(2y+x\right)}\)
\(\frac{4}{x-2y}=\frac{-4.10x.\left(2y+x\right)}{10x\left(2y-x\right)\left(2y+x\right)}=\frac{-40x\left(2y+x\right)}{10x\left(2y-x\right)\left(2y+x\right)}\)
\(\frac{x-y}{8y^2-2x^2}=\frac{x-y}{2\left(4y^2-x^2\right)}=\frac{x-y}{2\left(2y-x\right)\left(2y+x\right)}=\frac{5x\left(x-y\right)}{10x\left(2y-x\right)\left(2y+x\right)}\)
c ) MTC : \(\left(x+2\right)^3\)
\(\frac{6x^2}{x^3+6x^2+12x+8}=\frac{6x^2}{\left(x+2\right)^3}\)
\(\frac{3x}{x^2+4x+4}=\frac{3x}{\left(x+2\right)^2}=\frac{3x\left(x+2\right)}{\left(x+2\right)^3}\)
\(\frac{2}{2x+4}=\frac{1}{x+2}=\frac{\left(x+2\right)^2}{\left(x+2\right)^3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{x^2-16}{4x-x^2}=\frac{\left(x+4\right)\left(x-4\right)}{x\left(4-x\right)}\)
\(=\frac{\left(x+4\right)\left(x-4\right)}{-x\left(x-4\right)}=\frac{x+4}{-x}\)
b) \(\frac{x^2+4x+3}{2x+6}=\frac{x^2+3x+x+3}{2\left(x+3\right)}\)
\(=\frac{x\left(x+3\right)+\left(x+3\right)}{2\left(x+3\right)}\)
\(=\frac{\left(x+1\right)\left(x+3\right)}{2\left(x+3\right)}=\frac{x+1}{2}\)
c) \(\frac{\left(2x^2+2x\right)\left(x-2\right)^2}{\left(x^3-4x\right)\left(x+1\right)}\)
\(=\frac{2x\left(x+1\right)\left(x-2\right)^2}{x\left(x^2-4\right)\left(x+1\right)}\)
\(=\frac{2x\left(x-2\right)^2}{x\left(x+2\right)\left(x-2\right)}\)
\(=\frac{2x\left(x-2\right)}{x\left(x+2\right)}\)
\(=\frac{2x^2-4x}{x^2+2x}\)
d) \(\frac{x^3-x^2y+xy^2}{x^3+y^3}\)
\(=\frac{x\left(x^2-xy+y^2\right)}{\left(x+y\right)\left(x^2-xy+y^2\right)}=\frac{x}{x+y}\)
a) \(\frac{2x-2y}{x^2-y^2}=\frac{2\left(x-y\right)}{\left(x-y\right)\left(x+y\right)}=\frac{2}{x+y}\)
\(\frac{5}{2x^2+4xy+2y^2}=\frac{5}{2\left(x^2+2xy+y^2\right)}=\frac{5}{2\left(x+y\right)^2}\)
MTC : 2( x + y )2
=> \(\hept{\begin{cases}\frac{2x-2y}{x^2-y^2}=\frac{2}{x+y}=\frac{2\times2\left(x+y\right)}{\left(x+y\right)\times2\left(x+y\right)}=\frac{4x+4y}{2\left(x+y\right)^2}\\\frac{5}{2x^2+4xy+2y^2}=\frac{5}{2\left(x^2+2xy+y^2\right)}=\frac{5}{2\left(x+y\right)^2}\end{cases}}\)
b) \(\frac{x-y}{x^3-y^3}=\frac{x-y}{\left(x-y\right)\left(x^2+xy+y^2\right)}=\frac{1}{x^2+xy+y^2}\)
\(\frac{5}{2x^2+2x+2}=\frac{5}{2\left(x^2+x+1\right)}\)
\(\frac{6}{4x^3+4x+4}=\frac{6}{4\left(x^2+x+1\right)}=\frac{3}{2\left(x^2+x+1\right)}\)
MTC : 2( x2 + x + 1 )( x2 + xy + y2 )
=> \(\frac{1}{x^2+xy+y^2}=\frac{2\left(x^2+x+1\right)}{2\left(x^2+x+1\right)\left(x^2+xy+y^2\right)}=\frac{2x^2+2x+2}{2\left(x^2+x+1\right)\left(x^2+xy+y^2\right)}\)
=> \(\frac{5}{2\left(x^2+x+1\right)}=\frac{5\left(x^2+xy+y^2\right)}{2\left(x^2+x+1\right)\left(x^2+xy+y^2\right)}=\frac{5x^2+5xy+5y^2}{2\left(x^2+x+1\right)\left(x^2+xy+y^2\right)}\)
=> \(\frac{3}{2\left(x^2+x+1\right)}=\frac{3\left(x^2+xy+y^2\right)}{2\left(x^2+x+1\right)\left(x^2+xy+y^2\right)}=\frac{3x^2+3xy+3y^2}{2\left(x^2+x+1\right)\left(x^2+xy+y^2\right)}\)
a, \(\frac{2x-2y}{x^2-y^2};\frac{5}{2x^2+4xy+2y^2}\)
Ta có : \(x^2-y^2=\left(x-y\right)\left(x+y\right)\)
\(2x^2+4xy+2y^2=2\left(x^2+2xy+y^2\right)=2\left(x+y\right)^2\)
MTC : \(2\left(x-y\right)\left(x+y\right)^2\)
\(\frac{2x-2y}{x^2-y^2}=\frac{2\left(x-y\right)}{\left(x-y\right)\left(x+y\right)}=\frac{2\left(x-y\right)\left(x+y\right)}{2\left(x-y\right)\left(x+y\right)^2}\)
\(\frac{5}{2\left(x^2+2xy+y^2\right)}=\frac{5}{2\left(x+y\right)^2}=\frac{5\left(x-y\right)}{2\left(x-y\right)\left(x+y\right)^2}\)